Fuzzy returns in portfolio theory (method of triangular fuzzy numbers) - Bolshakova, Irina V. (Journal of the Belarusian State University. Economics, 2021)
The classical Markowitz problem of investment portfolio optimization is generalised to the case of fuzzy return rates modeled by fuzzy triangular numbers. The risks associated with investment are modeled using polymatroid constraints on risk diversification. A system of algorithms for searching for fuzzy optimal solutions based on the Mathematica package is proposed.
Keywords: Markowitz model; fuzzy triangular numbers; fuzzy returns; risk polymatroid